Study and Investigate Strength and Durability of Concrete Replaced with Silica Fume and Fly Ash A Review - Kumar, Ashok; Jain, Neeraj (International Journal of Scientific Research in Civil Engineering, 2022)
The last few decades are well thought-out to be the era of the self-compacting concrete and thousands of researches has been carried out. In India, the development of concrete possessing self-compacting properties is still very much in its initial stages. Over the past couple of years, few attempts were made still the cost of production of such concrete is a challenging issue for the present concrete engineers. Hence, in the present study an attempt is done to understand the effect of copper slag as a mineral admixture on the properties of self-compacting concrete. Hence, our attempt is to produce more economical, durable and sustainable SCC using mineral admixture.
Keywords: Self Compacting Concrete; Admixture; Silica Fume; Fly Ash; Durability Test; Strength Test